Role of extracellular matrix components in biofilm formation and adaptation of Pseudomonas ogarae F113 to the rhizosphere environment - Blanco-Romero, Esther; Garrido-Sanz, Daniel; Durán, David; Rybtke, Morten; Tolker-Nielsen, Tim; Redondo-Nieto, Miguel; Rivilla, Rafael; Martín, Marta (Frontiers in Microbiology, 2024)
Regulating the transition of bacteria from motile to sessile lifestyles is crucial for their ability to compete effectively in the rhizosphere environment. Pseudomonas are known to rely on extracellular matrix (ECM) components for microcolony and biofilm formation, allowing them to adapt to a sessile lifestyle. Pseudomonas ogarae F113 possesses eight gene clusters responsible for the production of ECM components. These gene clusters are tightly regulated by AmrZ, a major transcriptional regulator that influences the cellular levels of c-di-GMP. The AmrZ-mediated transcriptional regulation of ECM components is primarily mediated by the signaling molecule c-di-GMP and the flagella master regulator FleQ. To investigate the functional role of these ECM components in P. ogarae F113, we performed phenotypic analyses using mutants in genes encoding these ECM components. These analyses included assessments of colony morphology, dye-staining, static attachment to abiotic surfaces, dynamic biofilm formation on abiotic surfaces, swimming motility, and competitive colonization assays of the rhizosphere. Our results revealed that alginate and PNAG polysaccharides, along with PsmE and the fimbrial low molecular weight protein/tight adherence (Flp/Tad) pilus, are the major ECM components contributing to biofilm formation. Additionally, we found that the majority of these components and MapA are needed for a competitive colonization of the rhizosphere in P. ogarae F113.